2002
DOI: 10.1038/sj.bmt.1703358
|View full text |Cite
|
Sign up to set email alerts
|

Radiologically guided fine needle lung biopsies in the evaluation of focal pulmonary lesions in allogeneic stem cell transplant recipients

Abstract: Lung problems are common in allogeneic stem cell transplant (SCT) recipients. The aetiology is complex and includes infectious causes, immunological problems, pulmonary haemorrhage, adult respiratory distress syndrome (ARDS), and manifestation of malignant disease.1,2 Many pulmonary complications in allogeneic SCT recipients can now be managed effectively, although mortality is still considerable. Some potential treatments are either expensive

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 22 publications
(23 reference statements)
0
13
0
Order By: Relevance
“…The radiologic pattern of the pulmonary involvement also influenced the diagnosis, with malignant diagnoses being more common in patients with focal distribution of lung lesions and in patients with nodular or mass-like lesions. A large proportion of our patients had the above-mentioned clinical and radiologic features that increased the likelihood of obtaining a malignant diagnosis, which could explain the higher incidence of malignant diagnoses in our study than in some of the previously reported studies [6,8,[12][13][14]18,22,27].…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…The radiologic pattern of the pulmonary involvement also influenced the diagnosis, with malignant diagnoses being more common in patients with focal distribution of lung lesions and in patients with nodular or mass-like lesions. A large proportion of our patients had the above-mentioned clinical and radiologic features that increased the likelihood of obtaining a malignant diagnosis, which could explain the higher incidence of malignant diagnoses in our study than in some of the previously reported studies [6,8,[12][13][14]18,22,27].…”
Section: Discussionmentioning
confidence: 58%
“…Many previous articles evaluating the etiology of pulmonary lesions in immunocompromised patients have reported that infectious causes are more common than malignancy (21-46% vs. 9.3-27%); however, these studies included immunocompromised patients with diverse underlying etiologies such as HIV infection, primary immunodeficiency disease, and solid-organ transplantation, in addition to patients with haematologic malignancies [6,8,[12][13][14]18,22,27]. However, similar to the current study, three previous studies including only patients with haematologic malignancies found that neoplastic lung lesions were at least as common or more common than infections [5,9,19].…”
Section: Discussionmentioning
confidence: 99%
“…Imaging modalities are fluoroscopy, multidetector computed tomography (MDCT), and ultrasound [7]. Ultrasound is useful only where the tissue mass is in contact with the chest wall since the ultrasound beam does not pass through air and, hence, the aerated lung.…”
Section: Percutaneous Transthoracic Lung Biopsiesmentioning
confidence: 99%
“…Complications were observed in 18 of 71 patients (25%), with pneumothorax occurring in 14 patients (20%) and 4 patients (6%) requiring chest tube placement. Generally, TTNA in HSCT recipients with focal lung lesions has excellent potential to provide specific diagnosis, especially in IPA [67]. If TTNA is not diagnostic, SLB may be indicated since bronchoscopy is of limited use in evaluating peripheral lesions [32].…”
Section: Transthoracic Needle Aspiration (Ttna)mentioning
confidence: 99%